(untitled) (Revista Científica Compendium, 2014)
The purpose of this study was to characterize the credit programs offered by the INAPYMI to small and medium industries (PYMI) that belong to the manufacturing sector of the State of Yaracuy, period 20092013. This is a eld design, descriptive research. The sample was made of nine (9) active PYMI. A census was applied and the people from the institution were interviewed. The main results indicate that credit programs awarded by INAPYMI enjoy great prestige by PYMI owners and manager, even though there are institutional weaknesses such as excessive bureaucracy, discretion and resource delivery delay. It is necessary to dene a specic economic and business long-term strategy, with emphasis on manufacturing activity in order to improve the performance of the industrial sector in the region.